Extravasation of the contrast media during voiding cystourethrography in a long-term spinal cord injury patient - A. Kovindha (2018)
Objective: To present complications and pitfalls in voiding cystourethrography (VCUG) and introduce a guideline for performing VCUG in a long-term spinal cord injury (SCI) patient with neurogenic bladder dysfunction (NBD) and contracted bladder. Study design: A case report. Setting: Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand. Method: We describe a chronic C5tetraplegic man with NBD and contracted bladder, who developed autonomic dysreflexia (AD), gross hematuria and extravasation of contrast median during VCUG. Result: A foley catheter was retained after VCUG. AD was resolved and urine cleared after a week of continuous bladder irrigation. Conclusion: VCUG should be performed with caution in a long-term SCI patient with NBD and contracted bladder. Forceful pushing of the contrast media by the hand-injection method caused abrupt distention of the contracted bladder, damaged bladder mucosa and aggrevated AD. We suggest a guideline as follows: report bladder capacity and AD, if present, in an X-ray requisition form; use the gravity-drip method, stop the drip and drain the contrast media if a sudden headache and rising of blood pressure (BP) develop; observe urine colour, and report if bleeding or AD occurs. © 2005 International Spinal Cord Society. All rights reserved.